2013
DOI: 10.1002/jctb.4006
|View full text |Cite
|
Sign up to set email alerts
|

Advanced treatment of biologically pretreated coking wastewater by electrochemical oxidation using Ti/RuO2–IrO2 electrodes

Abstract: BACKGROUND: Electrochemical oxidation has attracted wide attention in wastewater treatment because of its strong oxidation performance and ease of control. This work investigated the feasibility of electrochemical treatment using a Ti/RuO 2 -IrO 2 anode as an advanced treatment of coking wastewater. The influential operating factors including current density (9.6-108.2 mA cm −2 ) and electrode gap (0.5-2.5 cm) were evaluated. RESULTS: The current density and electrodes gap had significant effects on COD and NH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…The electrochemical cell was equipped with three mixed metal oxide (MMO) titanium coated electrodes as anodes (RuO 2 ‐IrO 2 , Pt‐IrO 2 , PbO 2 ) and four uncoated Ti mesh electrodes as cathodes (Magneto Special Anodes BV, The Netherlands). Each electrode surface area was 4 × 6 cm, and the distance between the electrodes was adjusted to 0.6 cm, connected to the DC power supply adopting monopolar electrodes connection method . The electrodes were fixed to the underneath of a floating vessel made of Depron foam, with the top edge of the electrodes erected on the upper surface of the vessel bottom.…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical cell was equipped with three mixed metal oxide (MMO) titanium coated electrodes as anodes (RuO 2 ‐IrO 2 , Pt‐IrO 2 , PbO 2 ) and four uncoated Ti mesh electrodes as cathodes (Magneto Special Anodes BV, The Netherlands). Each electrode surface area was 4 × 6 cm, and the distance between the electrodes was adjusted to 0.6 cm, connected to the DC power supply adopting monopolar electrodes connection method . The electrodes were fixed to the underneath of a floating vessel made of Depron foam, with the top edge of the electrodes erected on the upper surface of the vessel bottom.…”
Section: Methodsmentioning
confidence: 99%
“…High levels of NH 4 + -N removal (95.0 %) was achieved along with moderate mineralization (60.0−80.0 %) with Ti/RuO 2 -IrO 2 electrodes as anodes in the advanced treatment of biologically pretreated coking wastewater. 1 BDD showed high current efficiency and low energy consumption in ammonia removal, attributed to its high oxygen evolution overvoltage and low chloride evolution overvoltage (1.5V vs. SCE). 37 Exposures to herbicides/pesticides were associated with an increased Parkinson's disease risk in a dose-response relationship in the univariate analysis.…”
Section: Hot Issuesmentioning
confidence: 99%
“…Furthermore, gas chromatography-mass spectrometry analysis indicated that this technique could be employed to eliminate biorefractory and toxic compounds such as azo dyes, phthalates, bisphenol-A, phenanthrene, indole, quinoline and pyrimidine in wastewater. 1,5 As a result, electrochemical oxidation related-research had attracted more and more attention in many fields, such as wastewater treatment, drinking water purification, disinfection, electrochemical determination and so on. 3,8−11 The limiting factor in implementing electrochemical technology for the effective degradation of organic pollutant is often the electrode material.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, elimination of ROC before being sent to the reuse system is an urgent need being long pursued. Different approaches have been studied in terms of polishing biological effluent, such as coagulation, ozonation, reverse osmosis and advanced oxidation processes …”
Section: Introductionmentioning
confidence: 99%
“…Different approaches have been studied in terms of polishing biological effluent, such as coagulation, ozonation, reverse osmosis and advanced oxidation processes. 6,7 Adsorption on activated carbon is proven to be an effective technology to remove organic pollutants from wastewaters, owing to the large surface area, economic viability and easy operational procedures. Nevertheless, the difficult and costly regeneration process limits its application, and exhausted carbon incurs a serious disposal problem.…”
Section: Introductionmentioning
confidence: 99%